2021
DOI: 10.1111/jbi.14229
|View full text |Cite
|
Sign up to set email alerts
|

Neither historical climate nor contemporary range fully explain the extant patterns of molecular diversity in marine species

Abstract: Aim Intraspecific diversity is a significant component of adaptive potential, and thus, it is important to identify the evolutionary processes that have and will continue to shape the molecular diversity of natural populations. This study aims to untangle the possible drivers of intraspecific molecular diversity by testing whether patterns of historical climatic stability or contemporary range position correlate with molecular diversity. Location South African coastline. Taxa The cape urchin (Parechinus angulo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 109 publications
1
9
1
Order By: Relevance
“…This distinction between drivers of genetic diversity highlights how global‐scale analyses may not capture biodiversity trends occurring at more localized spatial scales (Sax & Gaines, 2003). Our results also contrast with previous studies within South Africa, which suggest that mean SST (Phair et al, 2019; Teske et al, 2019) and range position (Nielsen, Beger, et al, 2021) are strong drivers of genetic diversity. However, these South African studies were conducted on single species, and thus cannot account for the large differences between species and the broad evolutionary processes shaping multi‐species diversity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This distinction between drivers of genetic diversity highlights how global‐scale analyses may not capture biodiversity trends occurring at more localized spatial scales (Sax & Gaines, 2003). Our results also contrast with previous studies within South Africa, which suggest that mean SST (Phair et al, 2019; Teske et al, 2019) and range position (Nielsen, Beger, et al, 2021) are strong drivers of genetic diversity. However, these South African studies were conducted on single species, and thus cannot account for the large differences between species and the broad evolutionary processes shaping multi‐species diversity.…”
Section: Discussioncontrasting
confidence: 99%
“…the abundant‐centre hypothesis; Eckert et al, 2008), and environmental gradients and habitat stability over time (Hewitt, 2000) play critical roles in determining intraspecific genetic diversity. However, the drivers of intraspecific variation across species have largely been tested in isolation, and most of the few studies that compared multiple drivers of genetic diversity did so at spatial scales too large to be informative for conservation (Manel et al, 2020; Nielsen et al, 2021; Wyborn & Evans, 2021). Multi‐species comparisons in particular have immense power to detect patterns in the spatio‐temporal variation of genetic diversity at global scales (De Kort et al, 2021), although patterns tend to differ between regions and systems (Gratton et al, 2017; Manel et al, 2020; Miraldo et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…For kelp, an additional constraint to stepping‐stone dispersal is the discontinuity of rocky substrate along this coastline. Contrarily to what was hypothesized, the impact of past range shifts might have not been a major driver of the species' genetic structure (Nielsen et al, 2021). The SDM estimated the past distribution of L. pallida even broader than today, with none of the present populations potentially affected by extinctions and recolonization processes.…”
Section: Discussionmentioning
confidence: 99%
“…26°S latitude) promotes powerful offshore advection of the Benguela current and represents a permanent dispersal barrier for numerous marine species inhabiting the region (Gunawickrama et al, 2020;Henriques et al, 2012Henriques et al, , 2014Henriques et al, , 2016Schulze et al, 2020) and is a general marine biogeographical break (Spalding et al, 2007). The impact of past climate-driven range shifts (also including sea-level variations) has not been recognized as a major driver of genetic structure in southwestern Africa (Nielsen et al, 2021), in contrast to what has been widely suggested in the Northeast Atlantic and the Southwest and Northwest Pacific (Assis et al, 2016(Assis et al, , 2018Fraser et al, 2009;Neiva et al, 2018;Song et al, 2021). Glacial advances could have not impacted coastal distributions, as the southern continental limit of Africa lies at ca.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation